Exercise and Cognitive Function: An Experimental Study of Young Children Following Taekwondo - Febriani, Nawang Wulan; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
At the maturity stage of children's cognitive function, it is a stage that needs to be considered in the development process. Taekwondo training itself is one of the exercises that is able to maximize development and improve the cognitive function of elementary school children. This study aims to determine the effect of taekwondo training on the cognitive function of elementary school children. The method used in this research is an experiment with a one group pre-test post-test design. The subjects in this study were 16 people, consisting of 8 men and 8 women with an age range of 7-11 years. The research instrument used was the Stroop Color child Test. The results of this study show that there is a significant influence from the results of taekwondo training on the cognitive function of elementary school children. This research concludes that taekwondo training has a significant influence on the cognitive function of young children. In other words, taekwondo training had a significant impact on the cognitive function of these children.